Pengukuran Keseimbangan Lintasan Produksi Kabel Low Voltage NYM di PT. XYZ - Nurisusilawati, Isnaini; Bahari, Silvina (nter of Execellence (COE) ICT Infrastructure, Smart Manufacture and Digital Supply Chain, 2022)
XYZ is a cable company of excellence in audio-video cable technology through research, production, and product development. PT. XYZ produces frequency cables, power cables, and low-voltage cables and its newest products are USB cables and CCTV cables. PT. XYZ is a company that uses a make-to-order strategy. To produce quality products with fast delivery, a production division is needed, where the division is in charge of designing the production process, and maintaining product quality in accordance with established quality standards. As a company with a high production capacity target, a good strategy and planning are needed to increase efficiency by reducing waste. Balancing the utility of each path can be done to reduce the waste of time that occurs. Based on observations of the NYM low voltage cable production process, there is still idle time at several work stations due to the production machine factor. It is often found that there are workstations that are idle while other stations are fully working. The results of the data were obtained and processed by comparing the two types of NYM products based on product performance measurements. The efficiency level of the 2×1.5 mm² NYM product with a length of 46,000 meters is more efficient than the NYM 3×1.5 mm² product with a length of 12,000 meters because the balance delay in the NYM 3×1.5 mm² product is longer. So the company needs to evaluate or reassess the balance of the NYM assembly line.